Influence of the cooling rate on the microstructure of Al-Cu-Si, Al-Si and Al-Zn alloys - Ceylan, M; Aksoy, I; Kuzucu, V; Balo, SN (Elsevier Science Sa Lausanne, 1997)
The dendritic microstructures and solidification morphologies of Al-Cu-Si and Al-Si alloy were explored. Phase comparisons of Al-Zn, Al-Si and Al-Cu-Si alloy samples according to their rapid or slow cooling rate were made by using X-ray diffraction techniques, differences in the crystal structures of each alloy sample not being found. From differential scanning calorimetry investigations it was found that the rapidly solidified Al-Cu-Si sample released greater heat energy than the ingot sample of the same alloy, and the rapidly solidified Al-Si and Al-Zn alloys released less heat energy than the ingot samples of the same alloys during the healing regime in a differential scanning calorimeter. (C) 1997 Elsevier Science S.A.
Keywords: cooling rates; microstructure; aluminium alloys